CHARACTERISTICS OF THE EDUCATIONAL INFRASTRUCTURE SUPPORTING EARLY CHILDHOOD EDUCATION - Eshonqulov , Rakhmatillo (Scientific practical conference, 2026)
Educational infrastructure plays a crucial role in the development of effective early childhood education systems. This article analyzes the characteristics of modern educational infrastructure that supports young children's learning and development. Special attention is given to current policies and plans that aim to improve preschool education through innovative teaching methods, digital technologies, and inclusive learning environments. The paper also examines examples from developed countries that have successfully implemented advanced infrastructure and educational strategies for young learners. Furthermore, the article highlights innovative pedagogical approaches such as play-based learning, digital learning environments, and community-based education models. The study concludes by offering recommendations for improving educational infrastructure to ensure equal access, quality learning environments, and sustainable development in early childhood education.